UNDERSTANDING CONSUMER ATTITUDES AND PURCHASE INTENTIONS IN E-COMMERCE: THE IMPACT OF WEBSITE QUALITY, TRUST, AND PERCEIVED RISKS - Preety; Ahlawat, Pardeep K. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The rapid expansion of e-commerce has transformed consumer shopping behavior, making online platforms a primary retail channel. This study investigates the influence of website quality, perceived benefits, perceived risks, trust, and privacy concerns on online shopping attitudes and purchase intentions. Using a quantitative approach, data from 500 online shoppers were analyzed through Structural Equation Modeling (SEM). Findings reveal that website quality, perceived benefits (e.g., convenience and discounts), and trust positively impact online shopping attitudes, which significantly drive purchase intentions. Conversely, perceived risks, including financial insecurity, product uncertainty, and privacy concerns, negatively affect shopping attitudes. Trust and website quality emerged as the strongest predictors of online shopping engagement. This research enhances consumer behavior literature by integrating psychological and technological factors into a comprehensive framework. It offers valuable insights for e-commerce businesses, emphasizing the importance of user-friendly website design, secure payment systems, and transparent data policies to foster trust. Policymakers should enforce stronger consumer protection regulations to reduce risks and promote online shopping adoption. Future research should examine the long-term evolution of consumer behavior and the role of AI-driven personalization in enhancing e-commerce experiences.